A staging scheme for the development of the scuttle fly Megaselia abdita. - Karl R Wotton (PLoS ONE, 2014)
Model organisms, such as Drosophila melanogaster, provide powerful experimental tools for the study of development. However, approaches using model systems need to be complemented by comparative studies for us to gain a deeper understanding of the functional properties and evolution of developmental processes. New model organisms need to be established to enable such comparative work. The establishment of new model system requires a detailed description of its life cycle and development. The resulting staging scheme is essential for providing morphological context for molecular studies, and allows us to homologise developmental processes between species. In this paper, we provide a staging scheme and morphological characterisation of the life cycle for an emerging non-drosophilid dipteran model system: the scuttle fly Megaselia abdita. We pay particular attention to early embryogenesis (cleavage and blastoderm stages up to gastrulation), the formation and retraction of extraembryonic tissues, and the determination and formation of germ (pole) cells. Despite the large evolutionary distance between the two species (approximately 150 million years), we find that M. abdita development is remarkably similar to D. melanogaster in terms of developmental landmarks and their relative timing.